How do you simplify (10 - 4 * 13+ 19) div 23(10−4⋅13+19)÷23 using order of operations? Algebra Expressions, Equations, and Functions PEMDAS 1 Answer Shwetank Mauria Apr 25, 2016 (10-4*13+19)-:23=-1(10−4⋅13+19)÷23=−1 Explanation: (10-4*13+19)-:23(10−4⋅13+19)÷23 = (10-52+19)-:23(10−52+19)÷23 = (29-52)-:23(29−52)÷23 = (-23)-:23=-1(−23)÷23=−1 Answer link Related questions What is PEMDAS? How do you use PEMDAS? How do you use order of operations to simplify 3(7-2)-83(7−2)−8? What are common mistakes students make with PEMDAS? How do you evaluate the expression 5[8+(3-1)]-25[8+(3−1)]−2? How do you simplify the expression 4(30-(3+1)^2)4(30−(3+1)2)? How do you evaluate the expression x^4+xx4+x if x=2? Is it okay to add first before subtracting in 4-6+34−6+3? How do you simplify (-3)^2+12*5(−3)2+12⋅5? How do you simplify (4-2)^3-4*8+21div3(4−2)3−4⋅8+21÷3? See all questions in PEMDAS Impact of this question 1524 views around the world You can reuse this answer Creative Commons License